Amino Acids and their Derivatives in Pathogenesis and Treatment of Liver Diseases - Nefyodov, I.I.; Karakosh, A.J.; Alufaini, M.A.; Karavay, P.A.; Karavay, N.L. (Journal of Hematology and Oncology Research, 2019)
A mini-review of literature data on the mechanisms of formation of the stock of free amino acids and their derivatives in liver pathology and methods for correcting metabolic imbalance
Keywords: amino acids; derivatives; liver pathology